Waste management in the chemical and petroleum industries - Bahadori, Alireza (John Wiley & Sons, Inc., 2020)
"Wastewater quality and the quantity produced determine the means of disposal and the costs of disposal. Suspended solids, total dissolved solids, and oxygen demand of produced waters have the most impact on wastewater treatment. Wastewater is a complex mixture of organic and inorganic compounds and the largest volume of by-product generated during chemical processing and both conventional and unconventional oil and gas recovery operations. The potential of oilfield produced water to be a source of fresh water for water-stressed oil-producing countries and the increasing environmental concerns in addition to stringent legislations on produced water discharge into the environment have made produced water management a significant part of the oil and gas business"-- Provided by publisher.
Keywords: Petroleum industry and trade -- Waste disposal.; Chemical industry -- Waste disposal.; Petroleum refineries -- Waste disposal.; elektronické knihy; electronic books